The role of the proteasome activator PA28 in MHC class I antigen processing - Sijts, Elisabeth Joanna Anna Maria; Sun, Yuansheng; Paschen, Annette; Schadendorf, Dirk (Molecular immunology, 2002)
The proteasome system is the major source for the generation of viral antigens and tumor antigens presented by major histocompatibility complex class I (MHC class I) molecules. A specific feature of the proteasomal antigen processing machinery is that five of its components are inducible by IFN-γ. Two of these are the α and β subunits of the proteasome activator PA28. Our results show that PA28 selectively up-regulates the presentation of viral MHC class I epitopes and that down regulation PA28 in tumor cells results in impaired presentation of a human TRP2 tumor antigen.